Effect of pre-grazing herbage mass and daily herbage allowance on perennial ryegrass swards structure, pasture dry matter intake and milk performance of Holstein-Friesian dairy cows - Roca-Fernandez, A. I.; O’Donovan, M. A.; Curran, J.; Gonzalez-Rodriguez, A. (Spanish Journal of Agricultural Research, 2011)
<span style="font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-bidi-font-family: ’Times New Roman’; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-bidi-language: AR-SA;" lang="EN-US">To maximize milk output and milk solids per hectare from grazing dairy cows it is necessary to identify the level of grazing swards in order to achieve high pasture dry matter intake (PDMI). The aim of this study was to investigate the effect of pre-grazing herbage mass (HM) and daily herbage allowance (DHA) on perennial ryegrass (Lolium perenne L.) swards structure, PDMI and milk performance. Sixty-four spring-calving Holstein-Friesian dairy cows were balanced and randomly assigned to one of four (n = 16) grazing groups (LL, LH, HL and HH) in a 2 × 2 factorial design. The treatments consisted on two pre-grazing HM, low (L- 1,600 kg DM ha–1) or high (H- 2,400 kg DM ha–1) and two DHA, low (L- 15 kg DM cow–1day–1) or high (H- 20 kg DM cow–1 day–1). Swards structure, PDMI and milk performance were examined across the grazing season. The low HM groups completed 9.5 rotations of average 22 days length compared to 6.5 rotations of 32 days for the high HM groups. Herbage utilization was greater (p < 0.001) when animals offered the low DHA (98.0%) compared to the high DHA (89.9%). Stem and dead DM yield (> 4.0 cm) were lower (p < 0.001) for the low HM (221 and 170 kg ha–1, respectively) than for the high HM (388 and 303 kg ha–1, respectively). The high DHA had higher (p < 0.001) milk output (19.5 kg day–1) and milk solids (1.46 kg cow–1). The highest milk output per ha and per cow was achieved by LH, with low post-grazing residuals and high sward quality.